2015
DOI: 10.1016/j.jpsychores.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

The role of insomnia in the treatment of chronic fatigue

Abstract: Improvement in insomnia severity had a significant impact on both improvement in fatigue and the ability to recover from a stressful situation. Insomnia severity may be a maintaining factor in chronic fatigue and specifically targeting this in treatment could increase treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 38 publications
5
31
2
1
Order By: Relevance
“…The latter is frequent in those with CFS [32,33] and while the precise cause of the sleep disturbance in CFS is unclear, it is not thought to be particularly correlated with previous levels of activity and exertion [34]. Nonetheless, treating insomnia and sleep disturbance has been shown to be beneficial for the fatigue in CFS [35]. As such attention to uncovering and treating sleep disturbance is recommended in patients with PAD with a view to improving their fatigue and overall QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is frequent in those with CFS [32,33] and while the precise cause of the sleep disturbance in CFS is unclear, it is not thought to be particularly correlated with previous levels of activity and exertion [34]. Nonetheless, treating insomnia and sleep disturbance has been shown to be beneficial for the fatigue in CFS [35]. As such attention to uncovering and treating sleep disturbance is recommended in patients with PAD with a view to improving their fatigue and overall QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies showed that insomnia is correlated with anxiety [58], depression [2,58], fatigue [2,49,51,58] and number of errors committed by nurses [11]. Therefore, appropriate treatment of insomnia will result in better outcomes.…”
Section: Insomnia Induced By Night Shift Work… 145mentioning
confidence: 99%
“…On the other hand, fatigue is known to be associated with subjective insomnia in many studies [36][37][38][39] . A cross-sectional study investigating the association between poor sleep quality, fatigue, and self-reported safety outcomes among emergency medical service workers revealed that sleep quality score was higher among workers with fatigue than those without fatigue 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study investigating the association between poor sleep quality, fatigue, and self-reported safety outcomes among emergency medical service workers revealed that sleep quality score was higher among workers with fatigue than those without fatigue 37 . Another study examining the effect of treatment for insomnia among patients with chronic fatigue demonstrated that improvement in insomnia severity had a significant impact on fatigue 39 . Thus, fatigue and subjective insomnia may affect each other bidirectionally.…”
Section: Discussionmentioning
confidence: 99%